A continuous roll-pulling approach for the fabrication of magnetic artificial cilia with microfluidic pumping capability. Issue 12 (23rd May 2016) - Wang, Ye; den Toonder, Jaap; Cardinaels, Ruth; Anderson, Patrick
Abstract : Magnetic artificial cilia capable of microfluidic flow generation fabricated using a novel roll pulling method with the potential for large-scale manufacturing. Abstract : Magnetic artificial cilia are micro-hairs covering a surface that can be actuated using a time-dependent magnetic field to pump or mix fluids in microfluidic devices. This paper presents a novel fabrication method to realize magnetic artificial cilia using a roll-pulling process, in which a cylinder decorated with micro-pillars rolls over a liquid precursor film that contains magnetic particles at a speed up to 1 m s −1, while a magnetic field is applied. Due to the interaction between the pillars and the liquid film, micro-hairs are pulled out of the film. In this way, surfaces with slender cone-shaped magnetic artificial cilia were produced. When integrated in a closed-loop channel, the artificial cilia were shown to be capable of generating substantial microfluidic pumping using external magnetic actuation. The spatial arrangement of the cilia can be varied by altering the layout of the micro-pillars on the roll surface. In addition, the final geometry of the individual cilia depends on the rheological properties of the precursor material in combination with the processing parameters of the roll-pulling process. A rheological study and fabrication tests were carried out for a range of precursor material compositions to obtain insight into the relation between precursor rheology and processing conditions on the one hand, and cilia geometry on the other hand. The development of this cleanroom-free, high speed and potentially large area method of production of artificial cilia is another step towards their implementation in real-life applications.